2015
DOI: 10.1016/j.enpol.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to energy efficiency in shipping: A triangulated approach to investigate the principal agent problem

Abstract: We provide the first analysis of the principal agent problem in shipping. We develop a framework that incorporates methodological triangulation. Our results show the extent to which this barrier is observed and perceived. The presence of the barrier has implications on the policy most suited to shipping. a b s t r a c tEnergy efficiency is a key policy strategy to meet some of the challenges being faced today and to plan for a sustainable future. Numerous empirical studies in various sectors suggest that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 40 publications
(61 reference statements)
1
86
0
Order By: Relevance
“…Numerous countries are involved in the case studies, including countries from Asia (Japan, Thailand, and China), Central Europe (Germany, the UK, Greece, Spain, and Italy) and America (Brazil, Venezuela, and the U.S). It is interesting to observe that some of the studies are the result of joint investigations by industry and academia concerning environmental sustainability [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Review Of Environmental Sustainability Literature For Portsmentioning
confidence: 99%
“…Numerous countries are involved in the case studies, including countries from Asia (Japan, Thailand, and China), Central Europe (Germany, the UK, Greece, Spain, and Italy) and America (Brazil, Venezuela, and the U.S). It is interesting to observe that some of the studies are the result of joint investigations by industry and academia concerning environmental sustainability [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Review Of Environmental Sustainability Literature For Portsmentioning
confidence: 99%
“…Approximately 14-31%, 4-9%, and 3-6% of the global emissions of NOx, SO X , and CO 2 , respectively, are from marine vessels (Gilbert et al, 2018;Taljegard et al, 2014). A report commissioned by the International Maritime Organization (IMO) assessed shipping to be responsible for approximately 1.1 Gt CO 2 in 2007, of which international shipping accounted for 0.9 Gt CO 2 (Anderson and Bows, 2011;Rehmatulla and Smith, 2015). The share has also been projected to increase: in the past two decades, the shipping sector has grown by 4.1%, 1.2 percentage points faster than the global gross domestic product (GDP) (Rehmatulla and Smith, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A report commissioned by the International Maritime Organization (IMO) assessed shipping to be responsible for approximately 1.1 Gt CO 2 in 2007, of which international shipping accounted for 0.9 Gt CO 2 (Anderson and Bows, 2011;Rehmatulla and Smith, 2015). The share has also been projected to increase: in the past two decades, the shipping sector has grown by 4.1%, 1.2 percentage points faster than the global gross domestic product (GDP) (Rehmatulla and Smith, 2015). The CO 2 emissions from shipping are projected in the range of 1.1-3.7 Gt CO 2 /yr in 2050, an up to 270% increase compared to 2007 in a business-as-usual scenario (Rehmatulla and Smith, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the EEDI and the SEEMP has the noteworthy aim, as recognized in the preamble of MEPC (2011a), to improve the energy efficiency for ships through a set of technical performance standards, which would result in reduction of emissions of any substances that originate from fuel and its combustion process, including those already controlled by Annex VI. These policies as well as policies aiming to improve the implementation of energy efficiency in shipping need to be carefully considered in order to ensure energy efficiency improvements whilst avoiding unnecessary burden on the shipping industry with ineffective regulation through technical, operational or market-based measures, as pointed out by Rehmatulla and Smith (2015). This is particularly pronounced in the definition of the reduction factor, as thoroughly and concluded that the reduction factor seems to be rigidly set and is likely to be either too lenient or too strict for the new ships, and proposed an alternative requirement that would allow for a feedback from the market and that is more likely to stimulate the improvements in energy efficiency and the CO 2 emission reduction.…”
Section: Introductionmentioning
confidence: 99%